A Caecal Lipoma with Pseudomalignant Features and Colo-colonic Intussusception - Ishak, Fatimah Mastura; Haron, Juhara (International Journal of Human and Health Sciences (IJHHS), 2020)
Gastrointestinal lipomas are rare benign non-epithelial tumours, usually single and slow growing. Most of colonic lipomas were detected incidentally during surgery, endoscopy or autopsy with incidence ranges from 0.2% to 4.4%. While lesion measures smaller than 2cm in diameter are usually asymptomatic, a larger lesion more than 2cm, can cause symptoms such as intestinal obstruction, rectal bleeding, intussusception, constipation, diarrhea or prolapse. Pre-operative diagnosis is challenging as symptoms and imaging mimic malignancy. Direct visualization of the submucosal lipoma can be done by endoscopy. It is seen as smooth, rounded yellowish polyps with a thick stalk or broad-based attachment. Its typical features are the “tent sign” (elevation of the mucosa over lipoma with biopsy forceps), “cushion sign” or “pillow sign” (pressing forceps against the lesion results in depression or pillowing of the mass) and the “naked fat sign” (extrusion of yellowish fat at the biopsy site). In some cases, with large sized flat shaped lesion and ulceration may lead to an impression of malignant lesion. If the endoscopic biopsy is not taken at accurate site, for example at inflamed mucosal of adjacent tissue, it can give false impression of “nonspecific colitis”. We describe a patient with persistent diarrhea and hematochezia who underwent open right hemicolectomy for the presumptive endoscopic and imaging diagnosis of caecal adenocarcinoma. However, histological examination confirmed benign caecal lipoma. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 122-126